The Influence of Personal Technical Ability and Work Experience on the Effectiveness of Using Accounting Information Systems With an Educational Background as a Moderation - Fitria, Amelia; Sari, Imelda (Santoso Academy Network, 2023)
The purpose of this study is to determine the impact of personal technical abilities and work experience on the effectiveness of using accounting information systems as a moderator with an educational background. This study was carried out at PT Komatsu And Marketing Support Indonesia. This study's sample consisted of 45 employees from PT Komatsu And Marketing Support Indonesia. The sampling technique employs a saturated sampling method in which the entire population serves as the research sample. The study's findings indicate that personal technical skills and work experience have a significant impact on the effectiveness of accounting information systems. Meanwhile, the relationship between personal technical ability and work experience on the effectiveness of using accounting information systems is unaffected by educational background